Association of triglyceride-glucose related indices with colorectal cancer risk among the US population: a cross-sectional study - Sen Niu; Chenshan Jiang; Xiaofei Miao; Ye Zhang; Zengyao Li; Tong Wang (BMC Cancer)
Abstract Background The predictive value of the triglyceride-glucose (TyG)-related indices for colorectal cancer (CRC) occurrence remains unclear. This study aims to establish the association between the TyG-related index and the risk of CRC among the US population. Methods The TyG index, along with the Triglyceride glucose-body mass index (TyG-BMI), Triglyceride glucose-waist circumference (TyG-WC), and Triglyceride glucose-waist-to-height ratio (TyG-WHtR), were calculated using data from CRC patients in the National Health and Nutrition Examination Surveys (NHANES) spanning 1999 to 2020. Weighted multivariate logistic regression and generalized additive models assessed the independent associations between these indices and CRC risk. Subgroup analyses and sensitivity tests evaluated the robustness and reliability of the findings. Receiver operating characteristic curve (ROC) was performed for predicting CRC risk using different TyG-related indices. Results Among 18,418 participants with an average age of 47.7 years, 126 were diagnosed with CRC. After adjusting for key confounding covariates, the TyG index was not significantly associated with CRC risk (OR = 1.32, 95% CI: 0.90–1.95, P = 0.1553), whereas significant positive associations remained for TyG-BMI, TyG-WC, and TyG-WtHR when analyzed as continuous variables. When categorized into quartiles, individuals in the highest quartile exhibited elevated CRC prevalence compared to the reference group (TyG: OR = 1.88, 95% CI: 0.86–4.12, P = 0.1632; TyG-BMI: OR = 2.80, 95% CI: 1.29–6.05, P = 0.0155; TyG-WC: OR = 2.71, 95% CI: 1.06–6.92, P = 0.0154; TyG-WtHR: OR = 3.62, 95% CI: 1.22–10.75, P = 0.0046), with statistically significant associations persisting for TyG-BMI, TyG-WC, and TyG-WtHR (all P < 0.05). Subgroup and interaction tests indicated that sex, age, hypertension, and diabetes did not significantly influence the association between TyG related indices and CRC risk (all P > 0.05). ROC analysis demonstrated that TyG-WtHR (AUC: 0.644, 95% CI: 0.6014–0.6917) outperformed other indices in CRC risk prediction (P < 0.001). Conclusions In the U.S. adult population, elevated TyG-WHtR index levels are significantly associated with a higher risk of developing CRC.